Pengaruh Model Role Playing Terhadap Minat dan Hasil Belajar Peserta Didik SMP Labschool Unesa 2 Surabaya pada Pelajaran IPS - Dhimas Bagus Virgiawan; Niswatin; Nurul Hasanah; Muhammad Irfandi Aditya (Program Studi S1 Pendidikan IPS, Universitas Negeri Surabaya, 2026)
This study aims to analyze the effect of the role-playing learning model on students' interest and learning outcomes in social studies learning. The study used a quantitative approach with a quasi-experimental nonequivalent control group design. The subjects were seventh-grade students of SMP Labschool Unesa 2 Surabaya, divided into an experimental class and a control class. Data collection was conducted using a learning interest questionnaire and a pretest–posttest learning outcome test. Data were analyzed using a normality test, N-Gain calculation, and hypothesis testing with a paired sample t-test. The results showed that the experimental class experienced an increase in learning interest from 62% to 84% and learning outcomes from 63% to 86%. In contrast, the control class did not show a significant increase, namely interest and learning outcomes from 65% to 64%. These findings indicate that role-playing is effective in increasing student engagement because students are directly involved in contextual role simulations. The implication is that the role-playing model can be an alternative social studies learning method to increase interest and learning outcomes.